Peningkatan Kesadaran Masyarakat tentang Kebersihan Lingkungan Pantai Wisata Uwe Lino melalui Penyediaan Sarana Kebersihan - Usy Nora Manurung; Wijanarko; Nickson Fajar Welisa; Wilan Qamari Atuka; Nurdiana; Susiana (ABDI WIDYA NUSANTARA: Jurnal Pengabdian Kepada Masyarakat, 2026)
Abstrak Uwe Lino Tourist Beach is located in Toaya Village, Sindue District, Donggala Regency. It is a natural tourist destination with great potential, especially for its beautiful coastal panorama, clear water, and beautiful location surrounded by coconut trees. However, this potential has not been optimally utilized due to low public awareness of the importance of maintaining environmental cleanliness. The purpose of this community service is to increase awareness and participation of the community and visitors in maintaining the cleanliness and sustainability of the Uwe Lino tourist environment. This service method is implemented through socialization and practice methods by conducting clean-up activities at Uwe Lino tourist beach. Before carrying out the service, the team first conducted a site survey and recorded the needs that needed to be prepared. The main target of this service activity was the cleanliness of Uwe Lino tourist beach. The results of the community service activities went well and smoothly, the community participated in socialization, beach clean-up actions, installation of banners urging people to maintain cleanliness and trash receptacles. Basically, the community is aware of the importance of maintaining beach cleanliness to preserve the environment and improve health quality. This community service activity has a positive ecological impact by reducing plastic waste found in the area, installing signs urging people to maintain cleanliness, and providing knowledge about the importance of maintaining environmental cleanliness.